ANALISIS ASUHAN KEPERAWATAN EFEKTIFITAS PERAWATAN LUKA DENGAN POVIDONE IODINE 10% DAN NACL 0.9% TERHADAP PENYEMBUHAN LUKA POST OPERASI ORIF - Gita Sekarsari, Andini; Widianingtyas, Nancy; Dwi Setyowati, Yovita (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Open Reduction Internal Fixation (ORIF) is a medical surgical procedure, which refers to open surgery to set bones, as is necessary for some fractures, internal fixation refers to screw and plate fixation to enable or facilitate healing. Post ORIF procedures can cause problems or complications such as tingling, pain, muscle strength, swelling or edema in the operated limb. Apart from that, skin problems or complications such as wound infections, wound dehiscence, wound viscera, surgical mumps (parotid). Wound care is carried out so that infection does not occur and wound healing is optimal. The aim of the research is that the author wants to compare the effectiveness of wound care after ORIF surgery using Povidone Iodine 10% and NaCl 0.9% in accelerating wound healing. The method used in this research was a case study of 4 respondents who had undergone ORIF surgery at RS X West Jakarta. The results of this study showed that there was no significant difference regarding wound conditions in wound care for post-ORIF surgery patients using 0.9% NaCl solution with 10% povidone iodine. There were differences between the four respondents regarding the length of the wound healing process and stitch removal.